Tutorials: an effective and interactive method of teaching undergraduate medical students - Kumar, R. Prahan; Kandhasamy, Kanimozhy; Chauhan, Ramesh Chand; Bazroy, Joy; Purty, Anil J.; Singh, Zile (International Journal Of Community Medicine And Public Health, 2016)
Background: There is growing concern among medical educators that conventional modes of teaching medical students neither encourage the right qualities in students nor impart a life-long respect for learning. The aim is to study the perception of undergraduate medical students about tutorials as a teaching learning method. Methods: A cross-sectional study was conducted among 7th semester M.B.B.S students of Pondicherry Institute of Medical Sciences. A tutorial session was conducted among 71 medical undergraduate students who were divided into 6 groups. The handouts were distributed to all the groups. Tutorial was conducted by trained faculty of the department of community medicine. At the end of the tutorial, a predesigned pretested questionnaire with responses prepared using Likert’s scale was given to all students to record their responses and feedback. Proportions of students’ response for various items were calculated and analysed using SPSS software. Results: Among the students who participated in the tutorial session 45 (63.4%) said that they could understand the topic better in tutorial. 49 (69%) students felt time management was better in a tutorial as compared to lecture. 55 (77.5%) expressed that tutorials are more interactive than a lecture. Conclusions: To conclude, the medical undergraduates felt that tutorial is an effective method of teaching learning process.